De-presciption: what, when and how? - Ahasan, HAM Nazmul; Hossain, Homayra Tahseen; Bala, Chandra Shekhar; Reza, Ishrat Binte (Journal of Bangladesh College of Physicians and Surgeons, 2020)
De-prescription or de-prescribing is a new idea in clinical medicine. This is the structured way of withdrawing of inappropriate medication supervised by a health care professional with the goal of managing polypharmacy and improving outcomes. It is estimated that half of older adult patients are treated with polypharmacy (five or more drugs). The prevalence of Polypharmacy in the elderly is higher, ranging from 30% to 70%, even reaching 90% in residents of some residential geriatric care facilities in developed nations. Polypharmacy in the elderly increases the risk of adverse reactions, inappropriate prescriptions, drug interactions, number of hospitalizations, costs, and even death. Polypharmacy and CNS drugs increase fall risk by about 50%. Withdrawal of psychotropic drugs reduced falls by 66%. There are different deprescribing models. These are focused especially on elderly patients as well as on specific specialties such as psychiatry. It includes meticulous evaluation of the patient, identifying potentially inappropriate medications, prioritizing drug discontinuation, performing the deprescription and monitoring the result bearing in mind the risks of deprescribing. J Bangladesh Coll Phys Surg 2020; 38(4): 185-190